1990
DOI: 10.1016/0022-0965(90)90032-4
|View full text |Cite
|
Sign up to set email alerts
|

The emergence of strategic knowledge activation in categorical clustering during retrieval

Abstract: NutzungsbedingungenGewährt wird ein nicht exklusives, nicht übertragbares, persönliches und beschränktes Recht auf Nutzung dieses Dokuments. Dieses Dokument ist ausschließlich für den persönlichen, nicht-kommerziellen Gebrauch bestimmt. Die Nutzung stellt keine Übertragung des Eigentumsrechts an diesem Dokument dar und gilt vorbehaltlich der folgenden Einschränkungen: Auf sämtlichen Kopien dieses Dokuments müssen alle Urheberrechtshinweise und sonstigen Hinweise auf gesetzlichen Schutz beibehalten werden. Sie … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

1993
1993
2020
2020

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 16 publications
(24 reference statements)
1
23
0
3
Order By: Relevance
“…Moreover, the influence seems to be bidirectional (cf. Flavell et al 2002;Hasselhorn 1990). That is, metamemory can influence memory behavior, which in turn leads to enhanced metamemory.…”
Section: Metamemory-memory Relationsmentioning
confidence: 94%
“…Moreover, the influence seems to be bidirectional (cf. Flavell et al 2002;Hasselhorn 1990). That is, metamemory can influence memory behavior, which in turn leads to enhanced metamemory.…”
Section: Metamemory-memory Relationsmentioning
confidence: 94%
“…Using the relationship between clustering and recall as an indication of strategic processing, only the oldest children could be considered to be strategic in Schneider's study (see Bjorklund and Jacobs, 1985;Frankel and Rollins, 1985;Hasselhorn, 1990 for similar evidence). Taken together, this research clearly demonstrates that differences in the meaningfulness of words considerably influences strategic processing.…”
Section: Knowledge Enables Use Of Particular Strategiesmentioning
confidence: 97%
“…Most of these studies focussed on the effects of conceptual or semantic knowledge on the use of organizational strategies in sort-recall tasks. Experimental manipulations concerned children's knowledge of categorical relations among items in terms of category typicality (e.g., Bjorklund, 1988;Corsale and Ornstein, 1980;Hasselhorn, 1990;Rabinowitz, 1984Rabinowitz, , 1988 or interitem associativity (e.g., Bjorklund and Jacobs, 1985;Frankel andRollins, 1985, Schneider, 1986).…”
Section: Knowledge Enables Use Of Particular Strategiesmentioning
confidence: 99%
“…Previous research on children's veridical memories for categorizable lists of items have shown that clustering in recall increases as the use of categorical relations at retrieval becomes as easy as the use of associative relations (e.g., Bjorklund & Jacobs, 1985) or becomes a preferred strategy for retrieval (e.g., Hasselhorn, 1990). In parallel, children's false memories for gist-consistent but unstudied categorical items may arise as children become better at abstracting the gist of categorical lists (e.g., Brainerd et al, 2002) or better at utilizing the categorical gist for retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…One account emphasizes age differences in conscious preference for one type of organization over the other. That is, as children get older, they become more aware of category organization as a useful memory strategy and more likely to apply it during retrieval (e.g., Hasselhorn, 1990;Schneider, 1986). Another account emphasizes age differences in the ease with which different semantic relations are activated.…”
mentioning
confidence: 99%